Quintilian on the Teaching of Greek and Latin Languages (De institutione oratoria) - Putkaradze, Ketevan (Bulletin of Akaki Tsereteli State University, 2025)
It is a known fact that in the 7th-6th centuries BC, when the Greeks massively left Greece to save themselves and their families in different countries, they managed to establish Greek settlements quite calmly for many reasons, among which we must consider the alleged knowledge of foreign languages. Marcus fabius Quintilianus also points to the necessity of teaching foreign languages in his work "De institutione oratoria”.